Moderate aortic valve stenosis in patients with left ventricular systolic dysfunction—insights on prognosis and the potential role of early aortic valve replacement - Huded, Chetan P.; Desai, Milind Y. (Journal of Thoracic Disease; Vol 9, No 10 (October 31, 2017): Journal of Thoracic Disease, 2017)
Aortic valve replacement (AVR) is the only definitive therapy for patients with hemodynamically significant aortic stenosis (AS), and the most pivotal issue in the longitudinal management of patients with AS is to identify the optimal timing for AVR when the benefits of the procedure most outweigh the risks.